Systems of parabolic variational inequalities without initial conditions - Lavrenyuk, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider a parabolic variational inequality without initial conditions. We construct a class of existence and uniqueness for a solution of this inequality. This class is defined by the exponential decrease or increase of solutions as t→−∞, depending on the coefficients of the inequality.